Risk factors for developing Mycobacterium kansasii lung disease: A case-control study in Korea. Issue 5 (February 2019) - Kim, Jin Hyoung; Seo, Kwang Won; Shin, Yongjoon; Oh, Ji Seon; Jun, Jae-Bum; Jeong, Joseph; Sim, Chang Sun; Baek, Seunghee; Lee, Taehoon; Ahn, Jong Joon
Abstract : Abstract: Previous studies have suggested that development of Mycobacterium kansasii lung disease (MKLD) was associated with COPD, pneumoconiosis, aging, male, immunosuppression, alcohol, malignancy, and certain occupations such as mining and sandblasting. However, previous studies were outdated and used non-comparative statistical methods. We aimed to determine the current risk factors for developing MKLD in Korea by using appropriate statistical techniques. Eighty-six MKLD patients were identified through a search of the Ulsan University Hospital database between January 2010 and December 2014. These cases were matched with 172 controls who had normal respiratory systems in a health examination during the same period (matching variables, age and sex; case: control ratio of 1:2). Clinical and demographic characteristics were gathered by reviewing the medical record and telephone survey. Multivariate logistic regression analyses were performed to evaluate risk factors for developing MKLD. Multivariate analysis showed that occupation in heavy industries (adjusted odds ratio (aOR) 6.41, 95% confidence interval (CI) 2.19−18.74, P = .001) and low body mass index (BMI) (aOR [per kg/m 2 ] 0.73, 95% CI 0.63−0.85, P < .001) were independent risk factors for development of MKLD. Educational attainment more than high school was associated with a lower risk of MKLD development (aOR 0.22, 95% CI 0.08−0.63, P = .005). Employees in heavy industry and low BMI are independent risk factors for development of MKLD in Korea.